2020
DOI: 10.1002/chem.201904217
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Recognition between Complementary Dinucleolipids To Control the Self‐Assembly of Lipidic Amphiphiles

Abstract: One of the major goals in systems chemistry is to create molecular assemblies with emergent properties that are characteristic of life. An interesting approach toward this goal is based on mergingd ifferent biological building blocks into synthetic systems with properties arising from the combination of their molecular components. The covalentl inkage of nucleic acids (or their constituents:n ucleotides,n ucleosides and nucleobases) with lipids in the same hybrid molecule leads, for example, to the so-called n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
(87 reference statements)
1
9
0
Order By: Relevance
“…While both the peptide and nucleic acid precursors appear capable of forming in prebiotic environments from simpler building blocks, it is their cooperative assembly, synergistic activity, and mutualistic functions that must emerge on the way to cellular life [15d,53] . Since synergy has also been observed between other prebiotically relevant molecular scaffolds, including NA‐lipid, [6b,11a,54] pep‐lipid, [11b,55] and sugar‐pep, [12a,56] we can expect to see rapid growth in complexity as systems chemistry approaches mature and grow [12b] . That will facilitate the creation of large repertoires of unique functions beyond those of living systems for critical future applications.…”
Section: Summary and Future Outlookmentioning
confidence: 99%
“…While both the peptide and nucleic acid precursors appear capable of forming in prebiotic environments from simpler building blocks, it is their cooperative assembly, synergistic activity, and mutualistic functions that must emerge on the way to cellular life [15d,53] . Since synergy has also been observed between other prebiotically relevant molecular scaffolds, including NA‐lipid, [6b,11a,54] pep‐lipid, [11b,55] and sugar‐pep, [12a,56] we can expect to see rapid growth in complexity as systems chemistry approaches mature and grow [12b] . That will facilitate the creation of large repertoires of unique functions beyond those of living systems for critical future applications.…”
Section: Summary and Future Outlookmentioning
confidence: 99%
“…[6][7][8] An important line in this area involves the development of chimeric systems that combine the properties of distinct biological building blocks, as a step towards replication, protometabolic networks and protocellular assemblies. [9][10][11][12][13] In the endeavour to mimic DNA's capacity for replication or, more generally, the capacity of living cells to self-reproduce, different forms of replication have been developed with both synthetic and biological molecules. [14][15][16][17][18] The literature is rich in processes that display autocatalysis, either through the product's catalysis of its own formation, 19 cyclic autocatalysis, 20,21 or in oscillatory reactions.…”
Section: Introductionmentioning
confidence: 99%
“…6–8 An important line in this area involves the development of chimeric systems that combine the properties of distinct biological building blocks, as a step towards replication, protometabolic networks and protocellular assemblies. 9–13…”
Section: Introductionmentioning
confidence: 99%
“…We now propose that alongside the development of NA-pep conjugate assemblies for new materials, an analysis of the formation of chimeras within complex mixtures, and particularly the selection of specific sequences through replication processes, will offer insight into their emergence in the early chemical evolution. Indeed, several studies have indicated that evolution in prebiotic environments, toward the origin of life, must have involved cooperative interactions among diverse classes of molecules (22)(23)(24)(25). Other studies, including the seminal works of Eigen (26) and Kauffman (27), have revealed the possible emergence of synergistic activity in prebiotic autocatalytic networks and, as a consequence, phase transitions toward beneficial cooperative and/ or selective behavior (28,29).…”
mentioning
confidence: 99%